2011
DOI: 10.1369/jhc.2010.956672
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Signals and the Loss of Lymphatic Vessel Hyaluronan Receptor-1 (LYVE-1) in the Early Pathogenesis of Laminin Alpha2-deficient Skeletal Muscle

Abstract: Congenital muscular dystrophy type 1A, a severe neuromuscular disease characterized by early-onset muscle weakness and degeneration, is caused by insufficient levels of laminin α2 (LAMA2) in the basal lamina surrounding muscle fibers and other cells. A better understanding of the molecular mechanisms leading to muscle loss is needed to develop therapeutic interventions for this disease. Here, the authors show that inflammation is an early feature of pathogenesis in Lama2-deficient mouse muscle, indicated by el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 50 publications
4
23
0
Order By: Relevance
“…Another down-regulation of the hyaluronan receptor was noted in lymphatic vessels during the early stages 24-48 h after mycoplasma infection (11). LYVE-1 is also lost from sinusoidal endothelial cells of the liver during inflammation (1) and from lymphatic vessels in the early phase of some murine models accompanied with muscle degeneration and inflammation, possibly due to the induction of TNFα (20). On the other hand, high molecular weight hyaluronan modulates inflammatory responses in macrophages: it inhibits LPS-induced inflammatory signalings in macrophages and microglia (2,16,21,22).…”
Section: Lyve1mentioning
confidence: 99%
See 1 more Smart Citation
“…Another down-regulation of the hyaluronan receptor was noted in lymphatic vessels during the early stages 24-48 h after mycoplasma infection (11). LYVE-1 is also lost from sinusoidal endothelial cells of the liver during inflammation (1) and from lymphatic vessels in the early phase of some murine models accompanied with muscle degeneration and inflammation, possibly due to the induction of TNFα (20). On the other hand, high molecular weight hyaluronan modulates inflammatory responses in macrophages: it inhibits LPS-induced inflammatory signalings in macrophages and microglia (2,16,21,22).…”
Section: Lyve1mentioning
confidence: 99%
“…Although any direct interaction of hyaluronan with LYVE-1 is unknown, the loss of LYVE-1 in macrophagic cells of the mesentery may be involved in the activation of inflammatory responses. In fact, Wardrop and Dominov (20) described how the disappearance of LYVE-1 in lymphatic vessels provides a sensitive biomarker to monitor active inflammatory or tissue damages.…”
Section: Lyve1mentioning
confidence: 99%
“…macrophage) infiltration and loss of LYVE-1 [7]. Death mechanisms related to the proinflammatory environment present within a week after birth could play a prominent role in the initial muscle loss in this disease.…”
Section: Discussionmentioning
confidence: 97%
“…Using a Lama2 -deficient mouse model ( Lama2 dy-W [6]), we found that expression of the proinflammatory cytokines TNFα and IL-1β is elevated in Lama2 -mutant muscles within 7 days after birth, prior to widespread muscle degeneration [7]. Lama2 -deficient muscle also had increased expression of tenascin C (TN-C), a matrix glycoprotein upregulated in pathological conditions such as inflammation, as well as reduced expression of lymphatic vessel endothelial hyaluronan receptor-1 (LYVE-1) in lymphatic capillaries within the muscles [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation